Hukum Penggunaan Aplikasi FaceApp dalam Perspektif Hukum Islam - Muhammad Yusram; Patahuddin, Askar; Ahmad Risal (Pusat Penelitian dan Pengabdian Masyarakat (P3M), Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2020)
This study aims to determine the legal use of the FaceApp application in terms of the Qur'an, sunnah, and opinions of the scholars, as well as its relation to the problem of changing God's creation. This study uses descriptive-qualitative with content analysis and library research technique. The results showed that: first, FaceApp is an application that can change face photos using technology in the form of neural networks that automatically produce very realistic facial transformations in photographs. The opinions of the scholars in the matter of changing God's creation are: 1) neutering humans and animals ; 2) changing physical form; 3) make a tattoo on the body; 4) change the religion of God. Second, the legal use of the FaceApp application in an Islamic perspective by the scholars was divided into two: some scholars banned the use of the FaceApp application and others allowed it. Nevertheless, the majority of the scholars chose to forbid it, based on the evidence in the Qur'an and related hadith and the number of violations and harms posed by this application.